Luteolin Ameliorates Hypertensive Vascular Remodeling through Inhibiting the Proliferation and Migration of Vascular Smooth Muscle Cells. (30th September 2015) - Su, Jie; Xu, Han-Ting; Yu, Jing-Jing; Gao, Jian-Li; Lei, Jing; Yin, Qiao-Shan; Li, Bo; Pang, Min-Xia; Su, Min-Xia; Mi, Wen-Jia; Chen, Su-Hong; Lv, Gui-Yuan
Abstract : Objectives . Preliminary researches showed that luteolin was used to treat hypertension. However, it is still unclear whether luteolin has effect on the hypertensive complication such as vascular remodeling. The present study was designed to investigate the effect of luteolin on the hypertensive vascular remodeling and its molecular mechanism. Method and Results . We evaluated the effect of luteolin on aorta thickening of hypertension in spontaneous hypertensive rats (SHRs) and found that luteolin could significantly decrease the blood pressure and media thickness of aorta in vivo . Luteolin could inhibit angiotensin II- (Ang II-) induced proliferation and migration of vascular smooth muscle cells (VSMCs). Dichlorofluorescein diacetate (DCFH-DA) staining result showed that luteolin reduced Ang II-stimulated ROS production in VSMCs. Furthermore, western blot and gelatin zymography results showed that luteolin treatment leaded to a decrease in ERK1/2, p-ERK1/2, p-p38, MMP2, and proliferating cell nuclear antigen (PCNA) protein level. Conclusion . These data support that luteolin can ameliorate hypertensive vascular remodeling by inhibiting the proliferation and migration of Ang II-induced VSMCs. Its mechanism is mediated by the regulation of MAPK signaling pathway and the production of ROS.